2013
DOI: 10.1002/eco.1404
|View full text |Cite
|
Sign up to set email alerts
|

The influence of watershed run‐off on the hydrology, forest floor litter and soil carbon of headwater wetlands

Abstract: The effects of land use and land cover (LULC) on aquatic systems have been extensively studied however less research has focused on headwater wetlands. This study was conducted to evaluate the effects of watershed land conversion and associated run-off on the hydrology and carbon cycling of headwater wetlands in coastal Alabama, USA. A total of 15 headwater wetlands were selected to reflect a range of surrounding LULC across coastal Alabama. Land use and soil data were utilized to estimate watershed run-off cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Measures of duration and average water level are commonly used in wetland restoration to set performance standards and evaluate success [116,117]. Although these metrics have been linked to wetland processes [118,119], our results indicate that the most relevant aspects of the hydrologic regime may depend on the system and process of interest [54].…”
Section: Complex Role Of Hydrology In Explaining Soc Stock Variabilit...mentioning
confidence: 79%
“…Measures of duration and average water level are commonly used in wetland restoration to set performance standards and evaluate success [116,117]. Although these metrics have been linked to wetland processes [118,119], our results indicate that the most relevant aspects of the hydrologic regime may depend on the system and process of interest [54].…”
Section: Complex Role Of Hydrology In Explaining Soc Stock Variabilit...mentioning
confidence: 79%
“…They are known to be transported in greenhouse materials and can be associated with the horticultural trade (Kraus et al 1999). In this study, this species was found on sites with sedimentation with little microtopography and standing water, conditions common in urban headwater wetlands (Barksdale et al 2014). E. planirostris were also found in sites that had other commonly occurring frog species (A. gryllus, A. terrestris, H. cinerea, H. chrysoscelis, L. clamitans, and P. crucifer).…”
Section: Discussionmentioning
confidence: 95%
“…With urbanization, wetlands usually experience important changes in hydrological conditions due to the proliferation of impervious surfaces that modify surface water and groundwater flows (Azous and Horner, 1997). In general, urban wetlands are characterized by higher water level fluctuations, shorter periods of water retention, and decreased recharge from groundwater (in the case of groundwater‐fed wetlands; Kentula et al, 2004; Barksdale et al, 2014), but these hydrological changes are often highly unpredictable (Ehrenfeld, 2003; Bhaskar et al, 2016). Depending on the specific local context, road development, grading alterations and the presence of rain collectors can disrupt flow patterns at the inlets or outlets of wetlands, thereby leading to increased flooding or drought (Ehrenfeld, 2000; Barksdale et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In general, urban wetlands are characterized by higher water level fluctuations, shorter periods of water retention, and decreased recharge from groundwater (in the case of groundwater‐fed wetlands; Kentula et al, 2004; Barksdale et al, 2014), but these hydrological changes are often highly unpredictable (Ehrenfeld, 2003; Bhaskar et al, 2016). Depending on the specific local context, road development, grading alterations and the presence of rain collectors can disrupt flow patterns at the inlets or outlets of wetlands, thereby leading to increased flooding or drought (Ehrenfeld, 2000; Barksdale et al, 2014). By releasing or intensifying anoxia stress in particular, drier or wetter wetland conditions often create new ecological plant niches (MacDougall and Turkington, 2005; Mayfield et al, 2010), which may contribute to their high beta diversity.…”
Section: Discussionmentioning
confidence: 99%